Acute respiratory distress syndrome. Issue 10 (October 2022) - Parikh aka Parmar, Tapan; Pilcher, David
Abstract: Acute respiratory distress syndrome (ARDS) is a heterogeneous lung disease that is triggered by pulmonary and non-pulmonary pathologies. It predominantly causes hypoxaemic respiratory failure and can lead to significant morbidity and mortality. Although ARDS remains underdiagnosed, 24% of mechanically ventilated patients in intensive care units and 33% of coronavirus disease (COVID-19) patients admitted to the hospital are reported to have ARDS. Despite recent advances in treatment, mortality remains at more than 30% for all ARDS patients and 43% for severe ARDS. The pathophysiology is complex and involves acute pulmonary and systemic inflammation, alveolar oedema, and de-recruitment which lead to ventilation-perfusion mismatch, reduced lung compliance and hypoxaemia. Similarities in the pathophysiology of COVID-19 ARDS outnumber differences from non-COVID-19 ARDS. Inhomogeneous distribution of transpulmonary pressure variation throughout the lungs in ARDS increases the risk of patient self-inflicted lung injury and ventilator-associated lung injury. Stratifying ARDS patients as per Berlin definition can help to recognize ARDS early, identify resource requirements and plan appropriate management. Treating the underlying cause, lung-protective ventilation and supportive care are the mainstays of clinical management. Multiple rescue therapies, novel treatments, and methods of facilitating individualized ventilation have been described but many require further validation; and appropriate patient selection is warranted.